2021
DOI: 10.16965/ijar.2021.138
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Corpus Callosum Size Using MRI In Nepalese Population

Abstract: Corpus callosum (CC) is the main fiber tract connecting the cortical and sub-cortical regions of the right, left hemispheres, and plays an essential role in the integration of information between the two hemispheres. By using magnetic resonance imaging (MRI), the dimensions of corpus callosum can be studied. In this cross-sectional quantitative study 80 cases of normal MRI head were selected for study over two months. T1 weighted sagittal spin-echo images with slice thickness of 6 mm, planned from an axial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The mean length of the corpus callosum in our study patients was 7.25 cm which was comparable with the results by Gnawali S et al [ 5 ] and Takeda S et al [ 6 ]. Similarly, the thickness of the genu, body, splenium, and rostrum were consistent with the findings described by Gnawali S et al and Takeda S et al The white matter changes are described as WMH by neuroimaging in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean length of the corpus callosum in our study patients was 7.25 cm which was comparable with the results by Gnawali S et al [ 5 ] and Takeda S et al [ 6 ]. Similarly, the thickness of the genu, body, splenium, and rostrum were consistent with the findings described by Gnawali S et al and Takeda S et al The white matter changes are described as WMH by neuroimaging in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of the studies have found the age-related thinning of CC. But the thinning has been found only modest in all of them [ [3] , [4] , [5] , [6] ]. The MRI has been a cornerstone in assessing the changes in the brain with age.…”
Section: Introductionmentioning
confidence: 99%
“…This study's findings underscore the potential clinical utility of assessing CCa parameters to aid in the diagnosis and grading of cerebral atrophy. Gnawal S., et.al;(2021) 18 : Corpus callosum (CC) serves as the primary fiber tract connecting the right and left hemispheres, facilitating crucial information integration. This cross-sectional quantitative study utilized magnetic resonance imaging (MRI) to investigate CC dimensions in 80 cases with normal MRI head scans over a twomonth period.…”
Section: Resultsmentioning
confidence: 99%
“…In this comprehensive review on MRI role in corpus callosum measurement have reviewed on many research articles and the outcome about corpus callosum measurement have to variation in length of corpus callosum at different age groups between both sexes. We compare the reviewed outcome with some different authors study Weis S. et.al; (1993), 7 Rajapkase J. et.al; (1996), 8 Dorion A. et.al; (2001), 9 Chiara N. et.al; (2004), 10 Van K. et.al; (2008), 11 Rizzo G. et.al; (2011), 12 Mohammad M. et.al; (2011), 13 Garel C. et.al; (2011), 14 Gao Y. et.al; (2018), 15 Kamal A. et.al; (2019), 16 Ping J. et.al; (2020), 17 Gnawali S. et.al; (2021), 18 Berman S. et.al; (2018), 19 Bayar O. et.al; (2021). 20 Their parameter was significant and population have variation in length of corpus callosum at different age group between both sexes.…”
Section: Discussionmentioning
confidence: 99%